THE IMPACT OF TRIPS AGREEMENT ON THE DEVELOPMENT OF INTELLECTUAL PROPERTY LAWS IN INDONESIA - Dewi Sulistianingsih; Raden Muhammad Arvy Ilyasa (Indonesia Private Law Review, 2022)
The purpose of this study is to analyze the impact of the TRIPs agreement on the development of intellectual property law in Indonesia. In the current era of globalization, the protection of intellectual property rights is related to global-scale trade at the international level. Protection of intellectual property rights becomes an important issue wherein the current era the development of technology, information and communication have developed very rapidly which gave rise to innovations. Therefore, it is necessary to study how the impact regarding the emergence of TRIPs and how the adjustments made by Indonesia so that the WTO/TRIPs Agreement is in accordance with the political dynamics of intellectual property law in Indonesia. This research is a doctrinal legal research based on secondary data. The materials used come from literature studies that focus on the study of intellectual property. Property rights become an important issue in the business world where business actors offering services or a product want to get guaranteed protection of intellectual property rights. One of the developments in intellectual property protection in Indonesia was affected by the Trade-Related Aspects of Intellectual Property Rights Agreement (TRIPs Agreement) which was found in the Uruguay Round agreement in the framework of GATT (General Agreement on Tariffs and Trade). Indonesia also agreed to the Uruguay round of GATT by adjusting intellectual property laws that have been regulated in TRIPs which marked the opening of provisions regarding TRIPs with in Indonesian legal system. Therefore it becomes Indonesia's obligation to harmonize and synergy exiscing the legal instruments and strict law enforcement in the protection of intellectual property in Indonesia.